2017
DOI: 10.1007/s40262-017-0579-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher Midazolam Clearance in Obese Adolescents Compared with Morbidly Obese Adults

Abstract: BackgroundThe clearance of cytochrome P450 (CYP) 3A substrates is reported to be reduced with lower age, inflammation and obesity. As it is unknown what the overall influence is of these factors in the case of obese adolescents vs. morbidly obese adults, we studied covariates influencing the clearance of the CYP3A substrate midazolam in a combined analysis of data from obese adolescents and morbidly obese adults.MethodsData from 19 obese adolescents [102.7 kg (62–149.5 kg)] and 20 morbidly obese adults [144 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 47 publications
5
27
1
1
Order By: Relevance
“…Lipophilic substances then have a larger volume of distribution and consequently a lower clearance. Bioavailability is also increased (Brill et al, 2014), possibly due to obesity-induced suppression of CYP3A activity (Brill et al, 2015;van Rongen et al, 2018).…”
Section: Role Of Obesitymentioning
confidence: 99%
“…Lipophilic substances then have a larger volume of distribution and consequently a lower clearance. Bioavailability is also increased (Brill et al, 2014), possibly due to obesity-induced suppression of CYP3A activity (Brill et al, 2015;van Rongen et al, 2018).…”
Section: Role Of Obesitymentioning
confidence: 99%
“…A recent population pharmacokinetic modeling analysis of midazolam found that midazolam clearance in morbidly obese adults was not predictive of clearance in obese adolescents. 94 Clinical studies typically do not collect and/or report duration of obesity, but this may be a variable of importance, for example, to compare similarity at baseline of demography in the treatment groups. More research is needed on drug transporters, drug-metabolizing enzymes, and their polymorphisms in both youth and adults to better predict how drug disposition and metabolism are affected along the spectrum of obesity, compounded over time with the accumulation of obesity comorbidities.…”
Section: Nonobesity Drugs Used In Hospitalized Pediatric Patientsmentioning
confidence: 99%
“…Some common target‐controlled infusion pumps deliver propofol using LBM for obese adults despite knowledge that propofol clearance is better calculated using TBM with allometric scaling . Dosing of midazolam in adolescents presenting for bariatric surgery remains problematic because of the lack of clear guidance for quantifying excess weight and using this to calculate the dose …”
Section: Current Dosing Regimens For Obese Childrenmentioning
confidence: 99%
“…11,12 Dosing of midazolam in adolescents presenting for bariatric surgery remains problematic because of the lack of clear guidance for quantifying excess weight and using this to calculate the dose. 13,14 3 | EMPIRICAL LINKS BETWEEN WE IGHT…”
Section: Cur Rent D Osin G Regimens For Obese Childrenmentioning
confidence: 99%